Les communautés religieuses et l'édition du manuel scolaire au Québec, 1765-1964 - Aubin, Paul (Groupe de recherche sur l'édition littéraire au Québec, 2001)
Keywords: Communautés religieuses; Enseignants; Édition

Légitimité de l’apostolat de l’édition: Le Lévrier et Fides - Cloutier, Yvan (Études d'histoire religieuse, 2001)
Keywords: Fides; Édition

Aspects de la thématique juive dans le Canadian Jewish News, édition de Montréal, 1977-1982 - Anctil, Pierre (Canadian Ethnic Studies / Études ethniques au Canada, 1984)
Keywords: Canadian Jewish News; Juifs

La réaction de l'épiscopat québécois à l'industrialisation de la presse, 1884-1914 - Guérin, Andréanne (Université Laval, 2006)
Keywords: Édition; Évêques

Le complexe éditorial des Jésuites et le contrôle de la lecture au Québec (1930-1960) - Vannucci, Simone (Mens, 2005)
Keywords: Communautés religieuses; Jésuites; Édition

Publishing in the Contact Zone: Linguistic Properties of the Book Publishing Field in Montreal - Shoumarova, Lina (Université Concordia, 2007)
Keywords: Anglophones; Francophones; Langue; Édition

Lieux et réseaux de sociabilité littéraire au Québec - Rajotte, Pierre (Nota bene, 2001)
Keywords: Clubs; Journalistes; Librairie; Écrivains; Édition

Trois grands artisans du diocèse de Montréal avec une carte comparée du diocèse en 1836 et en 1936 - Pouliot, Léon (Édition du Messager canadien, 1936)
Keywords: Bourget, Ignace; Diocèse; Fabre, Édouard-Charles; Lartigue, Jean-Jacques; Évêques

Marie de la Rousselière: histoire et influence - Hébert, Pierre-Maurice (Édition de l'Écho, 2008)
Keywords: Communautés religieuses; Pointe-aux-Trembles; Quartiers; Églises

Champ culturel et espace montréalais (I): la vie culturelle à Montréal avant 1960 - Bellavance, Guy; Poirier, Christian (Histoire de Montréal et de sa région, 2012)
Keywords: Art association; Expositions; Musique; Musée McCord; Musées; Radio; Théâtre; Université McGill; Édition

La sociabilité montréalaise au XIXe siècle: la présence des cultures francophone et anglophone - Lamonde, Yvan (Histoire de Montréal et de sa région, 2012)
Keywords: Anglophones; Clubs; Expositions; Famille; Francophones; Imprimerie; Musique; Places publiques; Théâtre; Édition

Social Relations in Nineteenth-Century Montreal: Two Cultural Streams - Lamonde, Yvan (Montreal: The History of A North American City, 2018)
Keywords: Anglophones; Clubs; Expositions; Famille; Francophones; Imprimerie; Musique; Places publiques; Théâtre; Édition

Cultural Field and Montreal Space (I): Cultural Life in Montreal - Bellavance, Guy; Poirier, Christian (Montreal: The History of A North American City, 2018)
Keywords: Art association; Expositions; Musique; Musée McCord; Musées; Radio; Théâtre; Université McGill; Édition

Docteur Bethune - Gordon, Sydney; Allan, Ted (Éditions L'Étincelle, 1973)
Keywords: Bethune, Norman; Médecine

Nécrologies des Filles de la Charité Servantes des Pauvres dites soeurs de la Providence de Montréal (1847-1891) (Providence, Maison-mère, 1921)
Keywords: Communautés religieuses; Soeurs de la Providence

The Case of the Canadians of Montreal Distressed by Fire (s.-é., 1865)
Keywords: Incendies

Women at the Hustings: Gender, Citizenship, and the Montreal By-Elections of 1832 - Bradbury, Bettina (Rethinking Canada: the Promise of Women’s History, 2011)
Keywords: Femmes; Élections

Indispensable but not a Citizen: the Housewife in the Great Depression - Baillargeon, Denyse (Rethinking Canada: the Promise of Women's History, 2006)
Keywords: Crise; Famille; Femmes

Women’s Workplaces: The Impact of Technological Change on Working-Class Women in the Home and in the Workplace in Nineteenth Century Montreal - Bradbury, Bettina (Rethinking Canada. The Promise of Women’s History, 2002)
Keywords: Femmes; Travail

FLQ: histoire d'un mouvement clandestin - Fournier, Louis (Lanctôt, 1998)
Keywords: Front de Libération du Québec

Working-Class Experience: Rethinking the History of Canadian Labour, 1800-1991 - Palmer, Bryan D. (McClelland & Stewart, 1992)
Keywords: Travail

The Family Economy and Work in an Industrializing City, Montreal in the 1870's - Bradbury, Bettina (Interpreting Canada's Past. Vol. 2: Post-Confederation, 1993)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

L'histoire des femmes au Québec depuis quatre siècles - Collectif Clio (Le Jour, 1992)
Keywords: Femmes

George-Étienne Cartier, bourgeois montréalais - Young, Brian (Boréal, 2004)
Keywords: Bourgeoisie; Cartier, George-Étienne

Les jeunes de la rue - Côté, Marguerite-Michelle (Liber, 1993)
Keywords: Itinérance

Women and Wage Labour in a Period of Transition: Montreal, 1861-1881 - Bradbury, Bettina (Canadian Labour History: Selected Readings, 1994)
NOTICE DG
Keywords: Famille; Femmes; Travail

Travail et syndicalisme: naissance et évolution d'une action sociale - Thwaites, James D. (Presses de l'Université Laval, 2002)
Keywords: Travail

Travail et syndicalisme: origines, évolution et défis d'une action sociale - Thwaites, James D. (Presses de l'Université Laval, 2007)
Keywords: Travail

Travail et syndicalisme: origines, évolution et défis d'une action sociale - Thwaites, James D. (Presses de l'Université Laval, 2014)
Keywords: Travail

Mère d'Youville: vénérable Marie-Marguerite du Frost de Lajemmerais veuve d'Youville, 1701-1771 fondatrice des Soeurs de la charité de l'Hôpital-Général de Montréal, dites soeurs grises - Ferland-Angers, Albertine (Centre Marguerite d'Youville, 1977)
Keywords: Communautés religieuses; Dufrost de Lajemmerais, Marie-Marguerite (Youville, Marguerite d'); Hôpital Général; Hôpitaux; Soeurs Grises

History of the School of Nursing of the Montreal General Hospital - Macdermot, Hugh E. (Alumnae Association, 1961)
Keywords: Femmes; Hôpitaux; Infirmières; Montreal General Hospital

Vie de Mme. d'Youville, fondatrice des soeurs de la charité de Ville-Marie, dans l'Ile de Montréal, en Canada - Faillon, Étienne-Michel (Éditions Magnificat, 1971)
Keywords: Communautés religieuses; Dufrost de Lajemmerais, Marie-Marguerite (Youville, Marguerite d'); Soeurs Grises

Mes tablettes: journal d'un apothicaire montréalais, 1820-1850 - Trudeau, Romuald (Leméac, 2016)
Keywords: Apothicaires

The journals of Yaacov Zipper, 1950-1982 : the struggle for Yiddishkeit - Zipper, Yaacov (McGill-Queen's University Press, 2004)
Keywords: Juifs

Le Collège de Montréal, 1767-1967 - Maurault, Olivier (s.é., 1967)
Keywords: Collège de Montréal; Communautés religieuses; Sulpiciens